Strengthening The Religious Character Education Program For Students Through Islamic Values - Fitriyadi Purba; Indra Prasetia; Amini Amini (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines the strengthening of students’ religious character education through Islamic values at SD Negeri 106232 Penggalangan. The research is grounded in the growing concern over moral decline, low discipline, and weakening spiritual awareness among elementary students, and the limited empirical studies in public primary schools. Using a qualitative approach with a descriptive case study design, data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data collection, data condensation, data display, and conclusion drawing/verification. The findings reveal that religious character education is implemented in a planned, structured, and sustainable manner through the integration of school culture, written policies, teacher role modeling, and religious habituation activities. These practices contribute to improvements in students’ self-control, discipline, responsibility, worship orderliness, and social interactions. Supporting factors include a strong school culture, teacher exemplarity, and parental involvement, while constraints involve limited time and students’ diverse backgrounds. This study contributes empirical evidence that Islamic values can effectively strengthen religious character education in public primary schools when implemented comprehensively and consistently.